An updated overview on the bacterial PhoP/PhoQ two-component signal transduction system - Meiqin Mao; Li He; Qingpi Yan (Frontiers in Cellular and Infection Microbiology)
The PhoP response regulator and the cognate sensor kinase PhoQ form one of the two-component signal transduction systems that is highly conserved in bacteria. The PhoP/PhoQ system is a crucial mediator of signal transduction. It regulates the expression of bacterial environmental tolerance genes, virulence factors, adhesion, and invasion-related genes by sensing various environmental signals in the host, including Mg2+, low pH, antimicrobial peptides, and osmotic pressure. In this review, we describe the PhoP/PhoQ system-induced signal composition and its feedback mechanism, and the abundance of PhoP phosphorylation in the activated state directly or indirectly controls the transcription and expression of related genes, regulating bacterial stability. Then, we discuss the relationship between the PhoP/PhoQ system and other components of the TCS system. Under the same induction conditions, their interaction relationship determines whether bacteria can quickly restore their homeostasis and exert virulence effects. Finally, we investigate the coordinated role of the PhoP/PhoQ system in acquiring pathogenic virulence.